2017
DOI: 10.3906/tar-1705-25
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vermicompost application on soil consistency limits and soil compactibility

Abstract: IntroductionSoil is a critical part of successful agriculture and is the original source of the nutrients that we use to grow crops. Healthy soils are essential for healthy plant growth, human nutrition, and ecosystem services (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…However, the rest of material is excreted out as “vermicastings” which accredit to the enrichment in soil porosity, aeration and production of soil aggregates. Earthworm's excretion in the form of vermicastings are rich in NPK, micronutrients and valuable soil microbes and consists more water-stable aggregates as compared to the nearby soil (Sari et al., 2017; Baghel et al., 2018). In addition, trough vermicomposting, bulk density, water holding capacity, pH, electrical conductivity, nitrogen, phosphorous and potassium content are better than those obtained with composting process (Doan et al., 2015; Rakkini et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the rest of material is excreted out as “vermicastings” which accredit to the enrichment in soil porosity, aeration and production of soil aggregates. Earthworm's excretion in the form of vermicastings are rich in NPK, micronutrients and valuable soil microbes and consists more water-stable aggregates as compared to the nearby soil (Sari et al., 2017; Baghel et al., 2018). In addition, trough vermicomposting, bulk density, water holding capacity, pH, electrical conductivity, nitrogen, phosphorous and potassium content are better than those obtained with composting process (Doan et al., 2015; Rakkini et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The liquid limit is influenced by soil texture, organic matter content, and the mineral content (Prabhakar & Satyeswararao, 2012;Ying, et al, 2021). The plastic limit is influenced by soil texture and organic matter content (Sari, et al, 2017). The adhesive limit is influenced by soil texture and organic matter content.…”
Section: Soil Consistencymentioning
confidence: 99%
“…The correlation test between the organic matter and parameter of consistency showed that organic matter was significantly and positively correlated with liquid, plastic, and adhesive limits (r=0.58 and P<0.05). This means that the increase in organic matter increases these limits (Sari, et al, 2017;Prabhakar & Satyeswararao, 2012). The studies showed that the increase in organic matter increases the liquid, plastic, and adhesive limits.…”
Section: Soil Consistencymentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizer and irrigation applications are effective and practical ways to control and improve yield and nutritional quality of crops for human consumption. In the current food production scenario, across major cropping systems of the world, crop yield is limited more by availability of nitrogen (N) and water resources than by the crop genetics (Sahin et al, 2002;Sinclair and Rufty, 2012;Kale et al, 2017;Sarı et al, 2017;Sarafi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%